Case studies on urban agriculture as a planning strategy for achieving sustainability in cities (Journal of Planner and Development, 2021)
Urban agriculture is one of the important urban uses of land in cities since the inception of cities and civilizations, but the great expansion of cities in the world during the twentieth century and the beginning of the twentieth century and the increase in the number of urban residents compared to the rural population has led to a decline in this use in favor of other uses. This decline in agricultural and green land areas in cities has negatively affected the environment, natural life and biological diversity in cities in addition to the great impact on the climate and the increase in temperatures and the negative impact on the economic side, since urban agriculture is an important pillar of the economy, especially for the poor groups that are adopted in their lives on this activity. Specialists in the field of environmental protection and urban and regional planning have recently warned about the importance of urban agriculture in cities and its effective role in achieving sustainability and food security for cities, combating climate change and other environmental problems associated with the decline of vegetation cover. This research aims to review global experiences in using urban agriculture to achieve urban sustainability and to clarify the important role of urban agriculture in achieving environmental balance in cities, confronting climate change and achieving self-sufficiency in cities.